Influence of perceived skill on the attitude of students after a Sport Education unit - Antonio Calderón; Diego Martínez de Ojeda; Isabel Mª Martínez (FEADEF, 2013)
The purpose of this paper was to analyze from the student and teachers' view, the synergies between perceived skill and attitude of students, after a Sport Education unit. To do this, it was measured pre and post the variables under study, through survey, teacher's log and interviews, of a tenth grade class (n = 16) and its teacher. Sport Education creates learning environments that promote autonomy and decision-making by students, increasing their positive attitudes towards physical education, also conditioned by perceived physical ability. Future research should be done together with other important educational and psychological variables